2011
DOI: 10.1210/me.2010-0424
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Activation of Extranuclear Signaling Pathways in Regulating p53 Expression in Vascular Endothelial Cells

Abstract: We previously showed that progesterone (P4) inhibited the proliferation of human umbilical vein endothelial cells (HUVECs) through a p53-dependent pathway. Now we investigated further the molecular mechanism underlying the hormone activity. In cultured HUVECs, P4 increased the protein levels of phosphorylated Src (p-Src), Raf-1, and ERK. The levels of p-Src and p-Src-progesterone receptor complex in HUVECs were increased by P4 treatment. These effects were blocked by pretreatment with a progesterone receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
2
38
1
Order By: Relevance
“…Previously, we have demonstrated that ERK is the downstream molecule of the Src involved in the progesterone-induced upregulation of p53 in HUVEC [12]. In the present study, we show that FA treatment increased the levels of p-ERK 1/2 (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Previously, we have demonstrated that ERK is the downstream molecule of the Src involved in the progesterone-induced upregulation of p53 in HUVEC [12]. In the present study, we show that FA treatment increased the levels of p-ERK 1/2 (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Expression of p21 is inducible by wildtype p53 but not mutant p53 [23]. Several studies have shown that expression of p53 in the cell can induce cell growth arrest through transcriptional activation of p21 [12,25,26]. In this study, we show that FA increased the levels of p53 protein (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations